Double Standards in Global Health: Medicine, Human Rights Law and Multidrug-Resistant TB Treatment Policy - Nicholson, Thomas (Health Hum Rights, 2016)
The human rights arguments that underpinned the fight against HIV over the last three decades were poised, but ultimately failed, to provide a similar foundation for success against multidrug-resistant TB (MDR-TB) and other diseases of the poor. With more than 1.5 million deaths since 2000 attributed to strains of MDR-TB, and with half a million new, and mostly untreated, MDR-TB cases in the world each year, the stakes could not be higher. The World Health Organization (WHO), whose mandate is to champion the attainment by all peoples of the highest possible level of health, recommended unsound medical treatment for MDR-TB patients in resource-poor settings from 1993-2002. Citing cost considerations, WHO did not recommend the available standard of care that had been successfully used to contain and defeat MDR-TB in rich countries. By acting as a strategic gatekeeper in its technical advisory role to donor agencies and countries, it also facilitated the global implementation of a double standard for TB care in low- and middle-income countries (LMICs), upending important legal and scientific priorities. This raises serious questions about whether the organization violated international human rights standards and those established in its own constitution. While calling for additional analysis and discussion on this topic, the authors propose that policymakers should reject double standards of this kind and instead embrace the challenge of implementing the highest standard of care on a global level.